Construction of reinforcement concrete for floor and slab / Syazlin Azwani Bahrim - Bahrim, Syazlin Azwani (Universiti Teknologi Mara, Perak, 2017)
Composite slab systems were first developed in the late 1930s for use in tall buildings. At that time, this technique brought a considerable dead-load reduction and was essentially seen as a substitute for traditional reinforced concrete slabs. The behaviour of composite slabs with decking has elements in common with both reinforcement and beam systems: decking with embossment or anchorages compares to reinforcement, whereas the decking itself is an element with bending rigidity similar to steel beams. Because of their efficiency and advantages, composite slabs were soon applied to a wide range of construction projects invariably based on structural steel framing.